IMPROVING THE TECHNOLOGY OF FUNCTIONAL PURPOSE DESSERT DISHES - BAL-PRYLYPKO, LARYSA; ANTONENKO, АRTEM; TOLOK, GALINA; TOLOK, SEMEN; GORKUN, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article describes the production technology, recipe composition of low-lactose ice cream. The expediency of using biologically active raw materials in the developed technology is substantiated. A set of data characterizing the quality of the developed dessert dish was obtained, and its high nutritional value was proven. On the basis of studies of the organoleptic indicators of the developed samples, a rational concentration of dietary supplements in the ice cream recipe was determined, which gives the developed food products improved taste properties and consistency compared to the control due to the use of biologically active raw materials. The developed technology of low-lactose ice cream has an increased content of dietary fibers, vitamins and minerals compared to traditional technology. The optimal ratio of components in the recipe of the developed dessert dish was experimentally confirmed. According to the organoleptic indicators, the obtained ice cream meets the established norms in terms of quality. The proposed method of dessert production makes it possible to obtain products of higher nutritional value compared to traditional technology. The quality of finished dessert products is characterized by organoleptic, physico-chemical, biochemical and microbiological indicators, and a comprehensive quality indicator was used to unambiguously assess the quality. The social effect of the introduction of the developed low-lactose dessert is to expand the range of meals for adults and children with an increased content of essential nutrients, improved consumer properties of the products, which will contribute to the preservation of the health of the population and the protection of the body from the negative effects of the environment. The developed culinary products can be recommended for the nutrition of people with partial or complete intolerance to lactose, in the daily diets of workers in heavy industry, living in ecologically polluted areas and all strata of the population.
Keywords: nutritional value; dessert; ice cream; food technology; vitamins; minerals